Toxic effect of cyclophosphamide on sperm morphology, testicular histology and blood oxidant-antioxidant balance, and protective roles of lycopene and ellagic acid - Çeribaşı, Ao; Türk, G; Sönmez, M; Sakin, F; Ateşşahin, A (My University, 2010)
In this study, the toxic effect of cyclophosphamide (CP) on sperm morphology, testicular histology and blood oxidant– antioxidant balance, and protective roles of lycopene (LC) and ellagic acid (EA) were investigated. For this purpose, 48 healthy, adult, male Sprague-Dawley rats were divided into six groups; eight animals in each group. The control group was treated with placebo. LC, EA and CP groups were given alone LC (10 mg ? kg ? every other day), EA (2 mg ? kg ? every other day) and CP (15 mg? kg ?week) respectively. One of the last two groups received CP + LC, and the other treated with CP + EA. All treatments were maintained for 8 weeks. At the end of the treatment period, morphological abnormalities of sperm, plasma malondialdehyde (MDA) levels and glutathione (GSH) levels, and GSH-peroxidase (GSH-Px), catalase (CAT) and superoxide dismutase (SOD) activities in erythrocytes, and testicular histopathological changes were examined. CP administration caused statistically significant increases in tail and total abnormality of sperm, plasma MDA level and erythrocyte SOD activity, and decreases in erythtocyte CAT activity, diameters of seminiferous tubules, germinal cell layer thickness and Johnsen’s Testicular Score along with degeneration, necrosis, immature germ cells, congestion and atrophy in testicular tissue. However, LC or EA treatments to CP-treated rats markedly improved the CP-induced lipid peroxidation, and normalized sperm morphology and testicular histopathology. In conclusion, CP-induced lipid peroxidation leads to the structural damages in spermatozoa and testicular tissue of rats, and also LC or EA have a protective effect on these types of damage.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Cyclophosphamide Lycopene Ellagic acid Sperm morphology Oxidative stress Testis histopathology